Performance assessment of a polyclinic heating and cooling system in a hospital building - Karakasli, Evren; Öztop, Hakan Fehmi; Hepbasli, Arif (Inderscience Enterprises Ltd, 2016)
The performance of a hospital building, heated by a natural gas-fired boiler system, was assessed by using energy and exergy analysis methods in this study. The analysis was performed from the primary energy production to the envelope of the building. In the evaluation, other parameters, such as total exergy input rate per area, total exergy input rate per volume and exergy flexibility factor were also utilised. It is found that overall energy and exergy efficiencies of the heating and cooling system were 13.4% and 1.35%, respectively. It may be concluded that in establishing energy policies, the exergy phenomenon should also be included because exergy is considered as a very useful and effective tool for buildings.
Keywords: building; energy and exergy analysis; energy conversion